A Magnetic Reduced Graphene Oxide Nanocomposite: Synthesis, Characterization, and Application for High-Efficiency Detoxification of Aflatoxin B1 - Chushu Zhang; Haixiang Zhou; Shining Cao; Jing Chen; Chunjuan Qu; Yueyi Tang; Mian Wang; Lifei Zhu; Xiaoyue Liu; Jiancheng Zhang (Toxins, 2024)
(1) Background: Safety problems associated with aflatoxin B1 (AFB1) contamination have always been a major threat to human health. Removing AFB1 through adsorption is considered an attractive remediation technique. (2) Methods: To produce an adsorbent with a high AFB1 adsorption efficiency, a magnetic reduced graphene oxide composite (Fe3O4@rGO) was synthesized using one-step hydrothermal fabrication. Then, the adsorbent was characterized using a series of techniques, such as SEM, TEM, XRD, FT-IR, VSM, and nitrogen adsorption–desorption analysis. Finally, the effects of this nanocomposite on the nutritional components of treated foods, such as vegetable oil and peanut milk, were also examined. (3) Results: The optimal synthesis conditions for Fe3O4@rGO were determined to be 200 °C for 6 h. The synthesis temperature significantly affected the adsorption properties of the prepared material due to its effect on the layered structure of graphene and the loading of Fe3O4 nanoparticles. The results of various characterizations illustrated that the surface of Fe3O4@rGO had a two-dimensional layered nanostructure with many folds and that Fe3O4 nanoparticles were distributed uniformly on the surface of the composite material. Moreover, the results of isotherm, kinetic, and thermodynamic analyses indicated that the adsorption of AFB1 by Fe3O4@rGO conformed to the Langmuir model, with a maximum adsorption capacity of 82.64 mg·g−1; the rapid and efficient adsorption of AFB1 occurred mainly through chemical adsorption via a spontaneous endothermic process. When applied to treat vegetable oil and peanut milk, the prepared material minimized the loss of nutrients and thus preserved food quality. (4) Conclusions: The above findings reveal a promising adsorbent, Fe3O4@rGO, with favorable properties for AFB1 adsorption and potential for food safety applications.